2021
DOI: 10.1177/0956797620975785
|View full text |Cite
|
Sign up to set email alerts
|

Massive Effects of Saliency on Information Processing in Visual Working Memory

Abstract: Limitations in the ability to temporarily represent information in visual working memory (VWM) are crucial for visual cognition. Whether VWM processing is dependent on an object’s saliency (i.e., how much it stands out) has been neglected in VWM research. Therefore, we developed a novel VWM task that allows direct control over saliency. In three experiments with this task (on 10, 31, and 60 adults, respectively), we consistently found that VWM performance is strongly and parametrically influenced by saliency a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…There has been substantial evidence over the last decade that salient distractors can be suppressed during visual search, particularly when the distractor features recur and are predictable (Chelazzi et al, 2019;Gaspelin & Luck, 2018b;Geng et al, 2019;Noonan et al, 2018). Recent work has provided further evidence that suppression is related to participant awareness of the salient distractor (Adams & Gaspelin, 2020;Adams & Gaspelin, 2021;Constant and Liesefeld, 2021;Won et al, 2019). However, the relationship between attentional suppression of salient distractors and memory for their features and confidence in awareness has not yet been assessed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been substantial evidence over the last decade that salient distractors can be suppressed during visual search, particularly when the distractor features recur and are predictable (Chelazzi et al, 2019;Gaspelin & Luck, 2018b;Geng et al, 2019;Noonan et al, 2018). Recent work has provided further evidence that suppression is related to participant awareness of the salient distractor (Adams & Gaspelin, 2020;Adams & Gaspelin, 2021;Constant and Liesefeld, 2021;Won et al, 2019). However, the relationship between attentional suppression of salient distractors and memory for their features and confidence in awareness has not yet been assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies, however, have shown a relationship between perceptual salience, attention, and awareness (Adams & Gaspelin, 2020;Constant & Liesefeld, 2021). Constant and Liesefeld (2021) used a parametric manipulation of salience and found a monotonic relationship between bottom-up saliency and the probability of memory for the item, although interestingly, the precision of the memory was not affected by saliency. Relatedly, Adams and Gaspelin (2020) found that participants were more likely to report awareness of a color singleton distractor from visual search trials with larger RT capture effects (Belopolsky et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As such, distractor suppression mechanisms may have been given distributional priority, their performance being preserved at the expense of target-selective mechanisms when neurometabolic demands exceeded the available supply. Although mainly speculative, this might be corroborated through additional manipulations to the attentional demands of both distractor and target processing-for instance, by assessing whether this hierarchy is maintained when the levels of target or distractor saliency are modified (see Constant & Liesefeld, 2021;Liesefeld et al, 2016;Töllner et al, 2011).…”
Section: Erp Pattern: Moderateintensity Exercise Enhances Attentional Resource Allocationmentioning
confidence: 99%
“…Furthermore, heterogeneous non-targets yield local feature contrast among each other and these salient non-targets therefore, generate peaks on the priority map that would compete with the target peak for attention allocations. Thus, display heterogeneity decreases the relative saliency of targets (see Constant & Liesefeld, 2021;Duncan & Humphreys, 1989). Accordingly, relying on saliency to find targets in highly heterogenous or sparse displays is not expedient, because it is unlikely that the priority map will guide attention to a target of low (relative) saliency.…”
mentioning
confidence: 99%